Phytomedical assessment of two Cymbopogon species found in Nkonkobe Municipality: toxicological effect on human Chang liver cell line - Beauty E. Omoruyi; Voster Muchenje (BMC, 2017)
Abstract Background Cymbopogon species are widely used as herbal remedies by the traditional healers living in Nkonkobe Municipality for the treatment and management of skin and respiratory infections. According to our survey, the plants seem to be very important because of the higher demands. Methods The leaves of C. validis and C. plurinodis were hydro-distilled and the resulted extracted oils were analyzed by GC/MS. Minimum inhibitory concentrations (MICs) ranging from 7.8 to 500.0 μg/ml of the extracted oils were tested against eight bacterial strains, using micro-well dilution method. The human Chang liver cell viability was determined using the CellTiter-Blue cell assay. Results GC-MS analysis of the C. validis essential oil amounted to 87.03%, major components identified were Linalyl alcohol (18.9%), 2-Nephthalenemethanol (6.67%), Longifolene (6.53%), Cubedol (6.08%). Total oil percentage of C. plurinodis was 81.47% and the main components were characterized as 3-Cyclohexane-1-ol (13.58%), Nerolidol (13.6%) and 2-Carene (12.6%). The essential oils from both plants were found to be active against the growth of Gram positive than the Gram negative bacterial tested. Lethal dose at 50 (LD50) of both plants showed 74.87 ± 1.41 and 81.66 ± 1.40 degree of toxicity at 24 h. Conclusion Both plants extracts were toxic to human Chang liver cell lines.